The who-when-why triangle of complementary and alternative medicine use among Portuguese IBD patients. Issue 4 (April 2017) - Portela, Francisco; Dias, Camila C.; Caldeira, Paulo; Cravo, Marilia; Deus, João; Gonçalves, Raquel; Lago, Paula; Morna, Henrique; Peixe, Paula; Ramos, Jaime; Sousa, Helena; Tavares, Lurdes; et al.
Abstract: Background: The use of complementary and alternative medicines is increasing among chronic patients, particularly those afflicted with inflammatory bowel diseases. Aim: This study aimed to address the prevalence of complementary and alternative medicines use among Portuguese inflammatory bowel diseases' patients. Methods: Patients were invited to fill an anonymous questionnaire concerning the use of complementary and alternative medicines. Results: Thirty-one per cent of the patients reported having used complementary and alternative medicines in the past, whereas 12% were using them by the time the questionnaire was administered. Fifty-nine per cent of the users did not share this information with their physician, whereas 14% and 8% discontinued their medication and periodical examination, respectively. Steroids prescription (OR = 2.880) and a higher instruction level (OR = 3.669) were predictors of complementary and alternative medicines use in this cohort. Conclusions: Roughly a third of Portuguese IBD patients had used CAM. Steroid treatment and an academic degree are associated with CAM use. Given the potential side effects and interactions, patient information about the benefits and limitations of conventional and complementary treatments should be reinforced.